Empowement of The Elderly Class on The Use of Sirsak (Annona Muricata Linn) Drops on The Reduction of Hypertention - Telova, Yurizki; Damayanti, Damayanti (JURNAL PENGMAS KESTRA (JPK), 2023)
Hypertension, which is usually known as high blood pressure, is a disorder in the blood vessels, which inhibits the supply of both oxygen and nutrients to the body. Hypertension is a dark killer or commonly called Silent killer, called a dark killer because this disease can kill victims who suffer from it without being accompanied by symptoms first. Some alternative traditional medicine therapies to reduce hypertension are soursop leaves (Annona Muricata Linn), because they contain potassium ions, because high potassium levels can increase sodium excretion, which can consequently reduce voulume and blood pressure. Hypertension is also common in menopausal women, because it is related to the depletion of ovarian follicles and also physical and psychological changes in menopausal women. This community service aims to educate elderly class mothers to use soursop leaves for non-pharmacological treatment to reduce blood pressure when given a decoction of soursop leaves to mothers, this service uses an accidental sampling prepost design approach, namely a treatment design using an experimental group only without a comparison or control group. Based on the results of the study seen from 30 respondents who were given soursop leaf decoction education for 1 week, 30 respondents understood or 100%, this shows that respondents understand about blood pressure in menopausal women after being given a decoction of soursop leaves.